An Audit Tata Kelola Teknologi Informasi di PT. SMOE Indonesia Menggunakan Framework COBIT 2019 - Mouf, Depri Al; Sari, Festy Winda (Politeknik Negeri Batam, 2024)
Information technology governance is an important part of the Company. Every Company that has implemented information technology in its activities must have good IT governance so that the company's business goals can be achieved with optimal utilization of information technology. This study examines the implementation of information technology governance at PT. SMOE Indonesia with the aim of improving information security. In this context, the information technology governance audit uses the COBIT 2019 framework. The audit was conducted to determine the domains and processes that exist at PT. SMOE Indonesia, the domains and processes used are APO13 and DSS05. The audit was conducted to determine the level of capability of each IT process running at PT. SMOE Indonesia